POLITICAL PARTICIPATION OF WOMEN IN ROMANIA - A BOTTOM-UP APPROACH - Diana Elena NEAGA (Challenges of the Knowledge Society)
In Romania the access of women to political decision making remains very low (around 10% women in Parliament). The main arguments used to explain this state of affairs are the following: the communist feminism (a contradiction in terms) which impose total obedience towards the state and a completely false and forced political empowerment of women which led to an arduous reverse after 1989 (Miroiu 2004;Vinkze 2006); the transition anti-socialist speech that militated in favor of the return to normality, understood as traditional patriarchy (Rueschemeyer, 1994), the gender-developed inequities of transition (Vincze 2006; Miroiu 2004, 2007); the lack of time as a citizenship resource (the double burden) (Lister, 2003). Even tough, what meanings do women attach to their status of citizens and how do they take part at political actions, in the context in which compelling structures, like patriarchy, the communist legacy and post-communist transition are overlapping their daily experiences, remains under studied in Romania. In order to fill this gap, in my paper I will present the result of a field work research (qualitative method interviews and focus-groups) focused on the way in which women live and experience citizenship, with accent on the perception and signification of their political participation. My arguments will be developed based on a constructivist approach which underline the relations and dependencies between agents (that give meaning to the social roles they play in my paper women from a region in Romania, Hunedoara county) and structures (mainly the patriarchal one).